Schneekundliche Arbeiten der Internationalen Glaziologischen Grönlandexpedition. - Marcel, de Quervain (Meddelelser om Grønland, 1969)
This report deals with the work carried out by the snow research section of the EGIG during the summer campaign 1959 and the subsequent wintering (1959/60). After a description of the operations and the topography of the working areas the following items are treated (Numbers referring to respective chapters): The annual accumulation in the range from Camp VI EGIG to Station Jarl-Joset (with some fragmentary observations to both sides beyond these stations) is studied. The methods consist of an analysis of all readings of the pole-markers set by EGIG and former expeditions, and of a stratigraphic examination of snow pits including the 40 m deep inclined shaft dug out by the Central-Greenland Expedition 1956- 57 (JEAN DUMONT). An east-west profile of the mean accumulation is presented (Abb. 32). The stratigraphic study implied the extensive production and examination of thin sections at the wintering station (Jarl-Joset) and in Swiss cold laboratories. Based on these observations an attempt is made to date the firn layers down to the bottom of the shaft and to evaluate the rate of settling and densification. At the main stations of EGIG the temperature of the névé is measured to a depth of about 20 m partly by means of electrical thermometers. Readings taken in subsequent years (1960, 1964) allow to evaluate variations in the surface temperatures. The temperature profile of the shaft Dumont reveals a slight decrease of temperature with depth, suggesting remainders of a colder period about a century ago. The temperature regime down to a depth of about 5 m was established during the wintering time. At the station Jarl-Joset, evaporation was continually measured during July 1959 and then again sporadically between April and June 1960. The net loss in July 1959 amounting to 4,3 mm H2O (hourly rates up to 40.10-3 mm) was superior to the accumulation of the same period (2 mm only). During the spring period of 1960 evaporation was distinctly lower (hourly values up to 13.10-3 mm). As a whole, evaporation is not an important factor of the mass balance of central Greenland. A particular investigation was devoted to the formation of the so called "summer facies" of the névé. It could be demonstrated that in summer, strong variations of the temperature gradient in the uppermost layer provoke a high rate of "constructive metamorphism" even in the absence of melting processes. Ice-petrofabric studies of thin sections from firn sampled in the shaft Dumont showed a distinct preferred orientation of the C-axis in the vertical direction. Using a photometric procedure a slight azimutal preference of the horizontal component of the axis is observed in most of the sections, but summing up all observations only a very weak indication of a preference is remaining. This is attributed to a predominant snow drift direction rather than to a rheological process. A series of snow profiles taken at station Jarl-Joset during the presence of the wintering group (August 1959 to July 1960) allowed a detailed study of the development of the three last annual deposits. This again resulted in an evaluation of the accumulation. The shaft Dumont offered an opportunity for studying the deformation of the neve crust down to 40 m depth. Marks set by the Central Greenland Expedition (DUMONT) in 1957 were remeasured by the EGIG in 1959. Despite the missing accuracy in the basic measurements ( 1957) it was possible to calculate figures for the horizontal and vertical shrinking of the shaft and to extrapolate the state which will be met with in 1965. A new set of marks was planted in the untouched wall of the shaft and surveyed for a future control.